Students' Perception of The Use of Shopee Barokah Based on Religiosity and Halal Lifestyle - Julia Hamdini Nasution; Nurlaila Nurlaila; Yenni Samri Juliati Nasution (Universitas Trunojoyo Madura, 2026)
The study results show that students who use Shopee Barokah find it easier to access Islamic information, such as prayer times, the Islamic calendar, and Islamic content, thus helping them apply religious values in their consumption activities. Furthermore, the feature also raises students' awareness of the importance of choosing halal products and avoiding transactions that potentially conflict with Sharia principles, such as the use of interest-based PayLater. Meanwhile, students who have not used Shopee Barokah generally still have limited information about the benefits of the feature, although they still strive to maintain halal principles in their daily lives. This study concludes that the use of Shopee Barokah positively supports the implementation of a halal lifestyle and strengthens the religiosity of FEBI students in their digital consumption activities. This research is expected to serve as a reference for the development of digital platforms oriented toward Islamic values and as a consideration for students in selecting shopping services that comply with Sharia principles.